(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Riparian forests serve as ecotones, marking the transition between terrestrial and aquatic ecosystems and differing from the surrounding landscapes. Managing these forests has been identified as a means to enhance various ecological functions, which play a key role in erosion control, as their vegetation stabilizes soil and reduces nutrient and carbon runoff into rivers. Additionally, riverbank vegetation helps mitigate flooding and improves water quality. Currently in Latvia, the Life project “LIFE IS SALACA” encompasses riverine habitat restoration and management, which demands an assessment of the initial conditions within the study region, necessary for characterising future dynamics of rivers and streams, as well as riparian forests and ground cover vegetation development. Therefore, the aim of this study was to describe and specify the current situation regarding ground cover vegetation diversity in riparian forest habitats in Salaca basin. To assess vegetation composition and structure, permanent 20×20 m (400 m²) sample plot was established in each study area. Vegetation surveys were conducted using the Braun-Banquet method, recording all vascular plant and moss species. The total projected cover (%) was estimated for four vegetation layers: tree layer (E3, trees >7 m), shrub layer (E2, shrubs and young trees 0.5–7 m), herb layer (E1, herbaceous plants, dwarf shrubs, and juvenile trees/shrubs <0.5 m), and moss layer (E0). Additionally, within these layers, the projected cover of each species was determined. The collected data will become an essential basis for monitoring riparian management processes, as well as provide valuable insight into the current vegetation diversity in the Salaca basin.